The process of designing for [online] learning: response to Bennett et al - Lee, Dabae (Educational technology research and development, 2021)
This article examines practical implications of the work by Bennett et al. (Educational Technology Research and Development 65(1):125–145, 2017) entitled, “The process of designing for learning: Understanding university teachers’ design work”. It addressed the knowledge gap of design practices of university faculty by conducting an extensive qualitative study with 30 interviewees. Three design practices reported that are incremental and iterative. Understanding these common design practices is critical to effectively and efficiently support faculty with transferring their instruction online when many institutions face the challenge of supporting a large number of inexperienced faculty with transferring instructions online. Based on the findings, three stages of support can be devised for before, during, and after sessions. Given the non-systematic cyclic design process of the teachers, need-based, just-in-time support and resources may be helpful. Although the reported process is not specifically for online learning design, the findings may contribute to establishing best practices for supporting faculty’s online learning design.